2022
DOI: 10.1126/sciadv.abm1847
|View full text |Cite
|
Sign up to set email alerts
|

Cellular shape reinforces niche to stem cell signaling in the small intestine

Abstract: Niche-derived factors regulate tissue stem cells, but apart from the mechanosensory pathways, the effect of niche geometry is not well understood. We used organoids and bioengineered tissue culture platforms to demonstrate that the conical shape of Lgr5 + small intestinal stem cells (ISCs) facilitate their self-renewal and function. Inhibition of non-muscle myosin II (NM II)–driven apical constriction altered ISC shape and reduced niche curvature and stem cell capacity. Niche curvature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 81 publications
1
23
0
Order By: Relevance
“…ISC growth-induced changes in the relative contact surface to the basement membrane could potentially alter the niche derived signaling strength, and hence, the outcome of the daughter cell fate. In line with this idea, it was recently shown that ISC shape, which is linked to its surface to volume ratio, changed the strength of the niche derived intracellular signaling activities of the ISC in mouse small intestine 44 .…”
Section: Discussionmentioning
confidence: 79%
“…ISC growth-induced changes in the relative contact surface to the basement membrane could potentially alter the niche derived signaling strength, and hence, the outcome of the daughter cell fate. In line with this idea, it was recently shown that ISC shape, which is linked to its surface to volume ratio, changed the strength of the niche derived intracellular signaling activities of the ISC in mouse small intestine 44 .…”
Section: Discussionmentioning
confidence: 79%
“…2a-c). Importantly, the extended lateral Golgi morphology coincided with the region harbouring ISCs and Paneth cells, which display a particular large lateral plasma membrane interface aiding their interactions 8 . Moreover, similar lateral Golgi morphology was also observed in the columnar ISCs of the colon (Extended Data Fig.…”
Section: Lateral Golgi Stacks Mediate Efficient Receptor Transportmentioning
confidence: 94%
“…1h). Moreover, amongst the ISCs located centrally within the niche, intensity of the Lgr5-linked eGFP expression, which correlates with stemness potential 8 , was higher in ISCs with two lateral Golgi as compared to ISCs with one lateral Golgi (Fig. 1i).…”
Section: Lateral Golgi Stacks Mediate Efficient Receptor Transportmentioning
confidence: 96%
See 1 more Smart Citation
“…These models are specifically a breakthrough for intestinal studies given the complex native crypt-villus geometry, which is required for efficient intestinal stem cells self-renewal and for the generation of biochemical gradients that mediate cell communication, differentiation and proliferation. 168 , 169 A variety of biomaterials have been used to create the scaffolds, ranging from biocompatible hydrogels based on natural or synthetic biopolymers with tunable physiochemical properties 170 , 171 to decellularized extracellular matrix. 172 Besides the biochemical scaffold composition, also its stiffness impacts the morphology and differentiation of intestinal epithelial cells.…”
Section: Advanced Intestinal Culture Systemsmentioning
confidence: 99%